2014
DOI: 10.1016/j.cmet.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clocks and Feeding Time Regulate the Oscillations and Levels of Hepatic Triglycerides

Abstract: Summary Circadian clocks play a major role in orchestrating daily physiology, and their disruption can evoke metabolic diseases such as fatty liver and obesity. To study the role of circadian clocks in lipid homeostasis, we performed an extensive lipidomic analysis of liver tissues from wild type and clock-disrupted mice, fed either ad libitum or night fed. To our surprise, a similar fraction of lipids (~17%) oscillated in both mouse strains, most notably triglycerides, but with completely different phases. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
290
5
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(322 citation statements)
references
References 43 publications
21
290
5
6
Order By: Relevance
“…In another study, lipidomics analyses revealed that about 17 % of lipids showed circadian oscillations in wild-type mice and in Per1 −/− /Per2 −/− mice fed ad libitum. Consistent with studies in human subjects (108) , TAG species were especially rhythmic, but their peak accumulation was shifted in clock gene-deficient animals (112) . Exposure to a high-fat diet also has a profound influence on diurnal variation in the liver metabolome (82,113) .…”
Section: Using Lipidomics To Characterise Metabolic Pathwayssupporting
confidence: 84%
“…In another study, lipidomics analyses revealed that about 17 % of lipids showed circadian oscillations in wild-type mice and in Per1 −/− /Per2 −/− mice fed ad libitum. Consistent with studies in human subjects (108) , TAG species were especially rhythmic, but their peak accumulation was shifted in clock gene-deficient animals (112) . Exposure to a high-fat diet also has a profound influence on diurnal variation in the liver metabolome (82,113) .…”
Section: Using Lipidomics To Characterise Metabolic Pathwayssupporting
confidence: 84%
“…6 I-L) of WT and PER1/2 null mice under the above-described conditions. In agreement with previous reports on clock-disrupted mice (11,16,32,33), Per1/2 −/− mice exhibited attenuated diurnal feeding rhythms and consumed more food during the light phase compared with WT mice (∼45% vs. ∼29% during the day and ∼55% vs. ∼71% during the night in PER1/2 null and WT mice, respectively). Short duration (i.e., 3 d) of high-fat diet in contrast to 6 wk of high-fat diet (38) did not significantly alter the daily feeding habits of WT mice.…”
Section: Diurnal Oscillations In Mitochondrial Respiration In Responssupporting
confidence: 80%
“…Clock-deficient mice (e.g., Clock mutant and Cry1/2 and Per1/2 double-KO mice) exhibit greatly attenuated diurnal feeding rhythms, because they consume more food during the light phase compared with WT mice (11,16,32,33). To examine whether feeding rhythms might play a role in the diurnal accumulation of CPT1 and PDH and consequently, mitochondrial respiration, we applied a nighttimerestricted feeding regimen on PER1/2 null mice.…”
Section: Diurnal Oscillations In Mitochondrial Respiration In Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extraction and transcript quantification by real-time PCR were carried out as previously described (Adamovich et al, 2014). Synthesis of cDNA was done using qScript TM cDNA SuperMix (Quanta Biosciences).…”
Section: Rna Preparation and Real-time Pcr Analysismentioning
confidence: 99%